Analysis of Conflict Control in The Development of UNESCO Global Geopark as Sustainable Tourism in Belitung Regency - Salsabil, Savia Resa; Kristianto, Yohanes; Ariana, Nyoman (Green Publisher Indonesia, 2023)
This study discusses conflict control analyze in sustainable tourism development in Belitung. The tourism development analyze were obtained using a qualitative descriptive approach. Data were collected through direct interviews with relevant stakeholders. The results of the analysis revealed three main conflicts that underlie the issues in sustainable tourism development, namely land disputes, partnership miscommunication or lack of synchronization, and mining problems. These three points give rise to various sub-issues and biased policies perceived by the local community and tourism actors and managers in Belitung Regency. Based on the findings, the researcher attempted to outline steps or strategies, including in the aspect of people: (1) Having a mindset of change and maturity, as well as concern for the next generation; (2) Willingness to introspect based on received criticism, and (3) Openness to criticism and suggestions. In the aspect of the planet: (1) Conducting education and training for the local community to raise awareness of tourism in each tourism destination. In the aspect of prosperity: (1) Establishing standardized indicators for income, price regulations, and well-structured business permits, accompanied by intensive supervision; (2) Supporting sustainable essence of alternative MSME funds; (3) Establishing government institutions to determine and regulate prices to remain competitive. In the aspect of peace: (1) Firmness in regulating various policies and avoiding overlapping.